ARRC: A random ray neutron transport code for nuclear reactor simulation. (February 2018) - Tramm, John R.; Smith, Kord S.; Forget, Benoit; Siegel, Andrew R.
Highlights: A new 3D neutron transport application (ARRC) is presented. ARRC implements the recently developed Random Ray Method (TRRM). A parallel domain decomposition scheme is developed and optimized. Validation is performed on several 2D and 3D benchmarks. ARRC is found to be a fast and accurate simulation tool for reactor modelling. Abstract: A massively parallel implementation of a recently developed technique for numerically integrating the transport equation, The Random Ray Method (TRRM) (Tramm et al., 2017), is applied to several large reactor benchmark problems. The implementation, which is part of a new development called The Advanced Random Ray Code (ARRC), is one of the first parallel implementations of TRRM. Our goal is to better understand the accuracy and performance characteristics of TRRM on massive scale problems, and to provide community software that facilitates further algorithmic development and potentially its application to a broader class of problems. Key features of ARRC include extreme memory efficiency, domain decomposition, a task based parallel structure, and the ability to efficiently utilize Single Instruction Multiple Data (SIMD) vector units. These attributes lead to efficient performance on modern high performance computer (HPC) architectures, enabling the detailed simulation of reactor cores in three dimensions.